Increases in Binocularity Periods with Treatment of Intermittent Central Suppression Contradict Suppression as Solely Inhibitory. - Hussey, Eric S. (Optometry & Visual Performance, 2015)
Intermittent central suppression (ICS), an intermittent loss of central visual sensation, has been associated with reading problems. In a prior report, ICS was treated using electronic rapid alternate occlusion as a stand-alone home therapy in a group of Job Corps students (n=26). The results from that study showed a decrease in suppression, a decrease in symptoms, and an increase in reading level (n=18). A further analysis of the decreased length of timed suppression periods versus the increased length of timed binocular periods suggests that the actual changes do not match changes that would be expected if suppression were exclusively an inhibition. If suppression is entirely inhibitory, anti-suppression therapy should decrease the inhibition, decreasing the length of suppression periods. However, decreasing an inhibition should not necessarily increase the length of non-inhibited, normal-sight binocular periods. The actual changes in suppression versus binocular periods in this group, however, showed an increase in length of binocular periods that was greater than the decrease in suppressed periods. This change is difficult to reconcile with the view of suppression as solely a cortical inhibition.